Short-Term Impacts of Targeted Cash Grants and Business Development Services: Experimental Evidence from Entrepreneurs in Burkina Faso - Michael Grimm; Sidiki Soubeiga; Michael Weber (Institute of Labor Economics (IZA), 2021)
Most support programs targeted at small firms in low- and middle-income countries fail to generate transformative effects at a large scale due to bad targeting, too little flexibility, and the limited size of the support, among others. This paper assesses the short-term effects of a randomized targeted Government support program to small and medium-size firms that have been selected based on a business plan competition. One group received large cash grants of up to US8,000, with flexible conditions of use. A second group received grants of an equally important size but earmarked to business development services and thus less flexible and with a required own contribution of 20 percent. A third group serves as a control group. All firms operate in agribusiness or related activities in a semi-urban area. An assessment of the short-term impacts shows that beneficiaries of cash grants engage in better business practices, such as formalization and bookkeeping. They also invest more. Yet, this does not translate into higher profits and employment. There is no effect on investment and business practices among beneficiaries of grants for business development services. Yet, both treatment groups show a higher ability to innovate relative to the control group. The results also show that cash grants cushioned the adverse effects of the COVID-19 pandemic. A further round of data collection will soon allow to assess the longer-term effects of both interventions which may differ from the short-term effects analyzed here as both interventions may need time to unfold their full effects.
Keywords: D22; O12; Q13; 330; firm support programs; cash grants; finance; matching grants; business development services; agribusiness; randomized controlled trial